A ludicidade em Cecília Meireles como sensibilização para a leitura na educação fundamental - Carvalho, Walkíria Pinto de (2006)
In our study, we have analyzed the ludicity in Cecília Meireles poetry. This theme deals with the conception of ludical, as human s language expression found in the poetic text. Thus, the main objective of this work is to analyze in what manner the ludicity of Meireles poetry can contribute to the sensitization and pleasure of reading in elementary course. For that to happen, we had to search the conception of ludical, poetry, poem and reading as well as Cecília Meireles contribution to the act of reading. We opted for a qualitative base research which description, analysis and interpretation is based on the stylistic structure and the production of meanings in the verses. The selection of these poems was based on the eagerness for knowing the reason of their recurrence in Portuguese Textbooks, while a teacher of the subject for eight years and also to know why students of Letras Course, from UFPB, have chosen these same texts very regularly during their traineeship in public schools. The results indicate an identification between poetry and cultural references of today s children and youths, starting form the act of playing alone, with the other and with the context. This information allows us to conclude that either one aspect or other, for being founded in a popular culture, it rescues the sensitization in the reader and this feeling emerges from all the memory someone has lived. It s from this connection that the pleasure of reading arises.